Selective CO2 adsorption and proton conductivity in the two-dimensional Zn(II) framework with protruded water molecules and flexible ether linkers - Phang, Won Ju; Lee, Woo Ram; Yoo, Kicheon; Kim, BongSoo; Hong, Chang Seop (ROYAL SOC CHEMISTRY, 2013)
A two-dimensional (2D) Zn(II) metal-organic framework with flexible aryl ether linkers and water molecules exposed to the pores was prepared. The supramolecular three-dimensional (3D) network is generated by the presence of extensive pi-pi contacts, which could be responsible for gas uptake. The water molecules and oxygen atoms from the flexible linkers create a polar environment within the integrated framework, leading to simultaneous selective CO2 adsorption and proton conductivity in the two-dimensional Zn(II) framework.
Keywords: METAL-ORGANIC FRAMEWORKS; CARBON-DIOXIDE; GAS; CONDUCTORS; SORPTION; CAPTURE; BINDING; STORAGE; CA